(6x+7)-(4+5x)=12

Simple and best practice solution for (6x+7)-(4+5x)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x+7)-(4+5x)=12 equation:


Simplifying
(6x + 7) + -1(4 + 5x) = 12

Reorder the terms:
(7 + 6x) + -1(4 + 5x) = 12

Remove parenthesis around (7 + 6x)
7 + 6x + -1(4 + 5x) = 12
7 + 6x + (4 * -1 + 5x * -1) = 12
7 + 6x + (-4 + -5x) = 12

Reorder the terms:
7 + -4 + 6x + -5x = 12

Combine like terms: 7 + -4 = 3
3 + 6x + -5x = 12

Combine like terms: 6x + -5x = 1x
3 + 1x = 12

Solving
3 + 1x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 1x = 12 + -3

Combine like terms: 3 + -3 = 0
0 + 1x = 12 + -3
1x = 12 + -3

Combine like terms: 12 + -3 = 9
1x = 9

Divide each side by '1'.
x = 9

Simplifying
x = 9

See similar equations:

| (4*2k)+3k-2= | | 9+10r-2=9r+35-3r | | 48x^2+24x+3=0 | | x=-60+2s | | 2y+110+35=360 | | 3(x-1)-24=2(-1-x) | | 2w^2-3w-27=0 | | 4x+18=58 | | 2x+40=110 | | 10x+6=64 | | 3[3f+1]=7[2f+9] | | 3(5-4t)-t=18 | | 2[3e-7]=5[6-e] | | 3[2d-9]+5d=105 | | 40x+60(x-2)=380 | | 8c-4[c+3]=8 | | 41-32=r | | 7[5b+6]=-63 | | 6[a-3]=24 | | 8.5a+6(20-a)=20(7) | | .5(60+x)=s | | 2x+6=4x+5+1 | | 8.5+6(20-x)=20(7) | | 4a+b=4 | | 0.75x+0.15(90-x)=90(0.35) | | 6x-10=64 | | 2p-4=44+8p | | Y=-x^2+20x-64 | | 2(2x-5)=2x-10 | | 7y-22=-28+6y | | 0.1r+0.2=0.6 | | 2x+15=45 |

Equations solver categories